Effect of red clover (Trifolium pratense L.) aqueous extract as an additive on nickel electrodeposition: Experimental and theoretical study - Inam M.A. Omar; Abdo Mohammed Al-Fakih (Arabian Journal of Chemistry, 2024)
Enhancements in nickel electrodeposition have been achieved using organic additives, some of which are not environmentally friendly and may produce undesirable deposits. Red clover leaf extract (RCLE) containing isoflavones was extracted aqueously from the Trifolium pratense L. plant. It was used as a green additive for nickel electrodeposition on a copper substrate in an acid-sulfate bath. The mechanism of Ni2+ electrodeposition was examined by anodic linear stripping voltammetry, cyclic voltammetry, and cathodic polarization. The surface morphology of the Ni2+ coatings were examined using SEM, EDX, XRD, and AFM. The adsorption of RCLE on the Cu substrate inhibited Ni2+ deposition and resulted in finer-grained, smoother, more uniform, and stronger hardness deposits. The corrosion protection of nickel coatings in a marine environment containing a 3.5 % NaCl solution was also investigated. The findings demonstrated that the addition of RCLE enhanced the corrosion resistance of Ni2+ deposition. The optimal structures of RCLE molecules and their active sites were examined using DFT computations. The results provide concise explanations of the precise atoms and functional groups responsible for the donation and acceptance of electrons. Thus, RCLE showed significant improvements in the process of nickel electrodeposition on a copper substrate in an acid sulfate solution.